A Summer Evening's Dream - Bellamy, Edward (Saga Egmont, 2023)
\'A Summer Evening\'s Dream\' (1898), a romantic, sentimental tale about second chances and first love, is a classic short story by the American author, Edward Bellamy, most famous for his socialist and utopian novel \'Looking 2000-1887\' (1888). Elderly Mary Rood and Robert Morgan were once childhood sweethearts, and both of them now live alone on the same street in the village of Plainfield. However, when Mr Morgan pays Mary a visit during a full moon, long-forgotten memories are rekindled. Sweet and heartwarming, this quick read will delight fans of Bellamy´s other works, such as ´Hooking Watermelons´ and ´Deserted´.